2015
DOI: 10.3238/arztebl.2015.0672
|View full text |Cite
|
Sign up to set email alerts
|

Shared Decision Making and the Use of Decision Aids

Abstract: When physicians treating cancer patients improve their competence in SDM by appropriate training, their patients may suffer less anxiety and depression. These effects merit further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 33 publications
1
70
0
3
Order By: Relevance
“…There is no agreement on what constitutes a clinically meaningful difference on the OPTION12. The sizes of the effects of SDM interventions on OPTION12, including decision aids and physician training across different specialties and in both simulated and clinical settings, range from 0.5 to 1.5 [ 41 , 64 , 65 ]. As most reported large effect sizes, we adopted an effect size of d = 0.8 in the sample size calculation.…”
Section: Methodsmentioning
confidence: 99%
“…There is no agreement on what constitutes a clinically meaningful difference on the OPTION12. The sizes of the effects of SDM interventions on OPTION12, including decision aids and physician training across different specialties and in both simulated and clinical settings, range from 0.5 to 1.5 [ 41 , 64 , 65 ]. As most reported large effect sizes, we adopted an effect size of d = 0.8 in the sample size calculation.…”
Section: Methodsmentioning
confidence: 99%
“…These tools include clinical calculators as well as recurrence assays utilizing gene expression profiles. In a recent randomized study involving patients with breast or colon cancer the use of decision aids was shown to decrease anxiety 14 . In our study, the patients with confirmed T3 MMR-P stage II colon cancer were prospectively enrolled to evaluate the impact and utility of the Oncotype DX Colon Cancer Assay on joint patient and physician treatment decisions and patient-reported roles in treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Ein wichtiges Element von PEF-Schulungen sind Elemente der Risikokommunikation, da sowohl Patienten als auch ihre Ärzte sich mit dem Verständnis von Statistiken schwer tun und diese leicht fehlinterpretieren [27]. tischen Haltung hin zu mehr Partizipation zu erreichen [23,26]. Neue Strategien setzen, statt wie bisher auf PEF-Gruppenschulungen von Ärzten, nun auch auf PEF-Einzelcoachingansätze sowie auf e-Tutorials zur PEF, die von den Ärzten ort-und zeitunabhängig absolviert werden können (www.pefmed.de).…”
Section: Indikationen Für Pefunclassified